2015
DOI: 10.3126/jmrd.v1i1.14240
|View full text |Cite
|
Sign up to set email alerts
|

Tillage and planting density affect the performance of maize hybrids in Chitwan, Nepal

Abstract: To find out whether the different tillage methods at different planting densities affect the performance of maize hybrids, an experiment was carried out at National Maize Research Program, Rampur during spring season of 2013 and 2014. The experiment was laid out in strip plot design with three replications having 12 treatments. The vertical factor was tillage with conservation tillage (No Tillage + residue=NT) and conventional tillage (CT) and the horizontal factor were genotypes (Rampur Hybrid-2 and RML-32/RM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
(9 reference statements)
0
6
0
Order By: Relevance
“…It has high yield potential, there is no cereal on the earth which has so immense potentiality and that is why it is called "queen of cereals" [1]. Maize is the second most important crop in terms of area and production after rice in Nepal [2]. The contribution of cereal crops to Agriculture Gross Domestic Product (AGDP) is about 49.41% whereas maize alone contributes 6.66% to AGDP [3].…”
Section: Introductionmentioning
confidence: 99%
“…It has high yield potential, there is no cereal on the earth which has so immense potentiality and that is why it is called "queen of cereals" [1]. Maize is the second most important crop in terms of area and production after rice in Nepal [2]. The contribution of cereal crops to Agriculture Gross Domestic Product (AGDP) is about 49.41% whereas maize alone contributes 6.66% to AGDP [3].…”
Section: Introductionmentioning
confidence: 99%
“…Maize (Zea mays L.) is considered as second most important crop in terms of area and production in Nepal and it is mainly grown in summer season (Karki, KC, Shrestha & Yadav, 2015). The area, production and yield of maize crop in 2015/16 are 891,583 hectare (ha), 2,231,517 metric tonnes (Mt), 2.50 Mtha -1 respectively in Nepal showing deficit of 610,000 Mt (CDD, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, T3 and T6 treatments are also non significant for TGW. Karki et al (2015) had also recorded highest test weight of 363.94 g in no till condition with mulching over the conventional tillage.…”
Section: Thousand Grain Weight (Tgw)mentioning
confidence: 95%
“…Similarly, T1 and T3 shows 64.22% and 40.09% higher grain yield relative to T5 treatments whereas T2 and T4 treatment increases 61.68% and 34.12% grain yield compare to T6 treatment. Karki et al (2015) had found higher grain yield 7012.18 kg ha -1 in no tillage with residue compare to conventional tillage (6037.59 kg ha -1 ). Hammad et al (2011), had recorded grain yield of 4.67 t ha -1 in combination of 6 number of irrigation with 150 kg ha -1 fertilizer application.…”
Section: Grain Yieldmentioning
confidence: 96%